Analisis Strategi Pengembangan Objek Wisata Danau Bandar Kayangan di Kota Pekanbaru - Sabri, Afisi (Komunitas Manajemen Kompetitif, 2015)
Abstract: Riau Province to develop tourism-development of the area to attract investors and provide easiness for them through regulations issued by the local government. Thus expected tourism in Riau Province can develop properly. One is the airport Heaven attractions Lembah Sari which is one of the sights of natural shades Pekanbaru. This type of research using descriptive technique is sample visitors 50 people taken by accidental, collecting data using questionnaires and descriptive data analysis. Based on the survey results revealed that the interest of society towards the development of attraction Banda Kayangan lake is quite good. Then the strategy of the Department of Tourism in developing attractions Kayangan Lake City to become a tourist attraction that can be reliable in Pekanbaru do several things: 1) Divide the airport Kayangan Lake area into several zones; 2) Make referrals development masterplan. There are several obstacles that are owned by the Department of Tourism in developing attractions Kayangan Lake City. It was of course very inhibits against the planned development. Existing barriers are: inadequate management, absence of interested investors to invest, existence of some corrupt officials to fund the development and the lack of oversight of contractors.